The burden of clostridium difficile infection in patients with liver cirrhosis - Despina Moraru; Andrada Dumitru; Sergiu Ioan Micu; Marilena Musat; Gabriel Preda; Popoiag Roxana Emanuela (Journal of Mind and Medical Sciences)
Clostridium Difficile Infection (CDI) has registered a dramatically increasing incidence in the general population over the past decades. Nowadays, Clostridium Difficile is the leading cause of hospital-acquired diarrhea in Europe and North America. Liver cirrhosis is the final stage of any chronic liver disease (CLD). The most common causes are chronic hepatitis C or B and viral coinfections, alcohol misuse, and nonalcoholic fatty liver disease (NAFLD). CLD and cirrhosis are listed among the ten leading causes of death in the US. Cirrhosis due to any etiology disrupts the homeostatic role of the liver in the body. Cirrhosis-associated immune dysfunction (CAID) leads to alterations in both inherited and acquired systemic and local liver immunity. CAID is caused by increased systemic inflammation and immunodeficiency and it is responsible for 30% of mortality rates all over the world. Clostridium Difficile infection frequently affects patients suffering from liver cirrhosis because of the high number of prolonged hospitalizations, regular use of antibiotics for the prevention or treatment of SBP, proton pump inhibitor (PPI) use, and an overall immunocompromised state. Clostridium Difficile is a Gram-positive bacterium responsible for the high morbidity and mortality rates in patients with cirrhosis, with an essential increase in a 30-day mortality.